The THE ATTRACTIVENESS OF GEOMETRY TRANSFORMATION MATERIAL LKPD BASED ON ETHNO-STEM FROM THE PERSPECTIVE OF STUDENTS - Farabi, Muhammad Al; Herwinsyah, Farha Ashiilah; Lathifa, Charirotul; Manggala, Ibrahim Sani Ali (Indonesian Journal of Educational Development (IJED), 2025)
Mathematics learning needs to be designed into attractive learning so that students can be motivated to learn and improve mathematics achievement. LKPD with Ethno-STEM learning approach becomes an alternative media that attracts students. This study aims to analyze the results of students' attractiveness responses to the use of Ethno-STEM based geometry transformation material LKPD. The data collection technique uses an interest questionnaire, then supported by student interviews. The study showed that the students' response to the use of geometry transformation material LKPD based on Ethno-STEM obtained an average score of 86.0% with the qualification “very attractive”. The assessment is based on the components of the attractiveness of the cover, content, images/illustrations, math material, learning related to local culture, and learning related to STEM elements. Ethno-STEM-based geometry transformation LKPD has a very attractiveness response from its users. For further research, it is recommended to test the effectiveness of geometry transformation material LKPD based on Ethno-STEM.